PEMBELAJARAN TINDAK TUTUR DIREKTIF LANGSUNG LITERAL DALAM FILM MY STUPID BOSS - A.Andriyani Asra; H.Andi Asnawi; Rahmita R (Jurnal Pendidikan Sang Surya, 2022)
The purpose of this study was to provide an overview of the literal direct directive speech acts contained in the film My Stupid Boss. The research method used was descriptive qualitative. The data from this analysis are in the form of sentences spoken by the characters in the form of direct literal directive speech acts. The data collection technique used is the listening and note-taking technique. The results obtained show that Upi Avianto's film My Stupid Boss contains direct directive speech acts which include types of speech acts of request, question, command, prohibition, granting permission and advice.